Nghiên cứu khả năng hấp phụ Cr(VI) từ dung dịch nước bằng than bùn Thừa Thiên - Huế - Sĩ, Hoàng Trọng; Hiếu, Đinh Quang (Vietnam Journal of Chemistry, 2012)
In this paper, the adsorption of Cr(VI) from aqueous solutions on Thua Thien-Hue peat was studied under both equilibrium and dynamic conditions in the concentration range of 2.5 - 10 mg/L. The peat was characterized by XRD, IR and isotherms of adsorption/desorption in nitrogen. The Cr(VI) was analyzed spectrophotometrically using diphenyl carbazide as as a complexing agent. The adsortion of Cr(VI) was found to be pH dependent. The adroption data could fitted to Freundlich adsorption isotherm. The adsorption process was endothermic in nature. The effect of various dose of peat was also discussed.